SOSIALISASI KURIKULUM PROTOTIPE DAN DINAMIKA PENDIDIKAN PADA REVOLUSI INDUSTRI ERA 5.0 DI YAYASAN AR RAHMAH KECAMATAN JABUNG KABUPATEN MALANG - Anita Kurnia Rachman; Indrawati Pusparini; Ike Dian Puspitasari (JPM PAMBUDI, 2022)
Community service activities carried out by IKIP Lecturer Budi Utomo aim to provide an understanding of the socialization of the prototype curriculum and the dynamics of education in the 5.0 era industrial revolution at the Ar-Rahmah Foundation. This foundation is located at Jl. Sidodadi No. 28 Bando Hamlet, Sukolilo, Jabung, Malang Regency, East Java. The Ar-Rahmah Foundation has several institutions under its auspices, MI and MTS. The implementation method used in this activity is the method of discussion and project based learning. This method is in accordance with the purpose of the prototype curriculum as a substitute for the previous curriculum. The prototype curriculum aims to change learning in Indonesia. Curriculum development helps efforts to recover learning caused by the COVID-19 pandemic. The service activity was carried out for three days which was attended by all MI and MTS teachers at the Ar-Rahmah Foundation. The results of this service activity, namely providing socialization and application of the prototype curriculum at the MI and MTS levels.